2006
DOI: 10.1002/uog.2829
|View full text |Cite
|
Sign up to set email alerts
|

Paraovarian/paratubal cysts: comparison of transvaginal sonographic and pathological findings to establish diagnostic criteria

Abstract: Objectives To describe the sonographic features of paraovarian cysts and to compare these features with pathological findings in order to define the best treatment options (surgical vs. conservative).Methods Fifty patients (mean age 48 (range, 14-68) years), each with a surgically proven paraovarian cyst, were retrospectively recruited. Preoperative transvaginal ultrasonographic B-mode and power Doppler observations were re-evaluated and histological reports were analyzed. Results All cysts were correctly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 19 publications
0
63
0
5
Order By: Relevance
“…11 Except mucinous cystadenoma which was multiseptate almost all adnexal tumors were reported as unilocular anechoic cyst. 12,13 In our study, the cysts ranged from 5 cm to 36 cm, mostly unilocular and echo-free in the postmenopausal women and were reported as either functional cysts or benign tumors. Ekerhovd et al reported that the risk of malignancy associated with unilocular echo-free cysts was not higher than 1.6%.…”
Section: 4mentioning
confidence: 60%
“…11 Except mucinous cystadenoma which was multiseptate almost all adnexal tumors were reported as unilocular anechoic cyst. 12,13 In our study, the cysts ranged from 5 cm to 36 cm, mostly unilocular and echo-free in the postmenopausal women and were reported as either functional cysts or benign tumors. Ekerhovd et al reported that the risk of malignancy associated with unilocular echo-free cysts was not higher than 1.6%.…”
Section: 4mentioning
confidence: 60%
“…The differential diagnosis of paratubal and paraovarian cyst by ultrasonography requires greater awareness and accuracy [7]. The dissocation of the cyst from the ovary when pushing the probe is a useful sign, called as ''Split sign'', for discriminating paraovarian masses [8]. Darwish et al [7], reported definite preoperative transvaginal sonography diagnosis in 44 % of the cases (52/118 patients).…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of residual of para-mesonephric ducts or more rarely of the mesonephric ducts causes the formation of paraovarian or paratubal cysts (5-20% of the adnexal masses) [5]. Such formations result constituted by totipotent epithelium celomatic cells.…”
Section: Discussionmentioning
confidence: 99%